Self-care assessment as an indicator for clinical supervision in nursing - Sílvia Marlene Monteiro Teixeira; António Luís Rodrigues Faria de Carvalho; Sandra Sílvia da Silva Monteiro Santos Cruz (Universidade Federal do Ceará, 2016)
Objective : to evaluate the needs of clinical supervision for nurses to assess the degree of dependence on self- care and planning of nursing interventions. Methods : analytical study, cross-cutting nature, collecting data from a sample of 110 patients. Results : it was shown the differences in the identification of the degree of dependence between registers and experts, as well as the selection of operations for each self-care and failures to the original assessment of the filling level (no evaluation self-care/no identification of the degree of dependence). Conclusion : there were gaps in the nursing process; they have proposed strategies such as clinical supervision sessions, training, case studies, protocols and guidance documents, to be included in a clinical supervision in nursing model.